Pengaruh Pajak, Tunneling Incentive, Kepemilikan Asing Terhadap Transfer Pricing dengan Ukuran Perusahaan Sebagai Variabel Moderasi: Studi pada Perusahaan Manufaktur Periode 2019 – 2023 - Iyam Maryam; Radhi Abdul Halim Rachmat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effect of Taxes, Tunneling Incentives, and Foreign Ownership on Transfer Pricing decisions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period, with Firm Size as a moderating variable. The phenomenon of transfer pricing in Indonesia has become a crucial issue due to potential state losses reaching IDR 1,300 trillion per year caused by profit shifting to low-tax jurisdictions. The research method uses a quantitative explanatory approach with a purposive sampling technique, resulting in a sample of 13 companies over 5 years of observation (65 observations). Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) via EViews 13 software. The partial test results indicate that the Tax variable has a significant effect on transfer pricing. Conversely, Tunneling Incentive has no effect on transfer pricing. Meanwhile, Foreign Ownership was found to have a significant effect on the company's transfer pricing decisions. This research contributes to regulators in strengthening the supervision of affiliated transactions, especially in the manufacturing sector which has a high vulnerability to price manipulation.